Fibromodulin: a master regulator of myostatin controlling progression of satellite cells through a myogenic program. Issue 8 (11th April 2016) - Lee, Eun Ju; Jan, Arif Tasleem; Baig, Mohammad Hassan; Ashraf, Jalaluddin Mohammad; Nahm, Sang‐Soep; Kim, Yong‐Woon; Park, So‐Young; Choi, Inho
ABSTRACT: Differentiation of muscle satellite cells (MSCs) involves interaction of the proteins present in the extracellular matrix (ECM) with MSCs to regulate their activity, and therefore phenotype. Herein, we report fibromodulin (FMOD), a member of the proteoglycan family participating in the assembly of ECM, as a novel regulator of myostatin (MSTN) during myoblast differentiation. In addition to having a pronounced effect on the expression of myogenic marker genes [myogenin ( MYOG ) and myosin light chain 2 ( MYL2 )], FMOD was found to maintain the transcriptional activity of MSTN. Moreover, coimmunoprecipitation and in silico studies performed to investigate the interaction of FMOD helped confirm that it antagonizes MSTN function by distorting its folding and preventing its binding to activin receptor type IIB. Furthermore, in vivo studies revealed that FMOD plays an active role in healing by increasing satellite cell recruitment to sites of injury. Together, these findings disclose a hitherto unrecognized regulatory role for FMOD in MSCs and highlight new mechanisms whereby FMOD circumvents the inhibitory effects of MSTN and triggers myoblast differentiation. These findings offer a basis for the design of novel MSTN inhibitors that promote muscle regeneration after injury or for the development of pharmaceutical agents for the treatment of different muscle atrophies.—Lee, E. J., Jan, A. T., Baig M. H., Ashraf, J. M., Nahm, S.‐S., Kim, Y.‐W., Park, S.‐Y., Choi, I. Fibromodulin: a master regulator of myostatin controlling progression of satellite cells through a myogenic program. FASEB J. 30, 2708‐2719 (2016). www.fasebj.org